The Impact of Digital Financial Services on Financial Literacy in South Kalimantan, Indonesia - Suryani, Sri; Hariyono, TA; Adha, Syamsul; Sucipto, Sucipto; Jahri, Muhammad (Yayasan Sembilan Pemuda Indonesia, 2025)
The rapid advancement of digital financial services has reshaped the global financial ecosystem, offering enhanced accessibility and efficiency while also requiring users to possess a certain level of financial and digital literacy. This study aims to examine the impact of digital financial services on financial literacy in the city of Banjarmasin, South Kalimantan, Indonesia. Employing a quantitative research design, data were collected from 100 users of mobile and internet banking services at Bank Kalsel through structured questionnaires. Analysis was conducted using descriptive and simple linear regression methods. The findings reveal a strong positive relationship between digital financial services and financial literacy, with an elasticity coefficient of 8.172 and a correlation coefficient (R) of 0.662. The coefficient of determination (R² = 0.438) indicates that 43.8% of the variation in financial literacy is explained by digital financial services. These results underscore the importance of digital financial inclusion, technology adoption, and service quality in enhancing users' financial knowledge, skills, and behavior. The study recommends integrated efforts from the government, financial institutions, and digital service providers to develop inclusive, user-friendly, and secure digital platforms, supported by targeted financial education programs to promote financial empowerment and reduce socio-economic disparities in South Kalimantan.